Experimental evaluation and numerical modeling of the mechanical performance of OSB sandwich panels manufactured with trapezoidal core. (4th April 2022) - Barbirato, Guilherme Henrique Ament; Junior, Wanley Eduardo Lopes; Martins, Rômulo Henrique; Soriano, Julio; Fiorelli, Juliano
Highlights: Development of an unconventional material using forest biomass by-products. OSB sandwich panel has great potential for applications in civil construction. Finite element model adequately predicted the deflection and failure of the panel. The stiffness ratio of the longitudinal and transverse directions was around 1.6. Abstract: The development of materials using forest biomass by-products has presented a viable alternative to replacing conventional materials and a great potential for the reuse of waste by-products. This study aimed to evaluate experimentally and by computational modeling, the mechanical performance of OSB (Oriented Strand Board) panels stiffened by the trapezoidal core according to the bending direction. By the cross-section of the panels manufactured with strands of balsa wood waste and castor oil polyurethane resin, the influence of the core direction on the flexural stiffness and ultimate load capacity was evaluated. Bending performance tests showed that stiffness in the longitudinal direction was 56% greater than in the transversal direction. For this same approach and referring to the elastic-linear segment, the computational modeling by Finite Element Analysis showed a superiority of 66% for stiffness in the longitudinal direction. Regarding the deflections and predictions of critical regions for the failure of the panel, an appropriate accuracy of the computational models adjusted for the material's nonlinearity and orthotropy. The OSB sandwich panels reached the minimum normative requirements for structural purposes, presenting great potential for applications in civil constructions, due to their efficient bending stiffness added to the benefits of a bio-based waste product